A glimpse of the future in animal nutrition science. 1. Past and future challenges - Tedeschi, Luis Orlindo; Almeida, Amelia Katiane de [UNESP]; Atzori, Alberto Stanislao; Muir, James Pierre; Fonseca, Mozart Alves; Cannas, Antonello (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 2017)
If the world population continues to increase exponentially, wealth and education inequalities might become more pronounced in the developing world. Thus, offering affordable, high-quality protein food to people will become more important and daunting than ever. Past and future challenges will increasingly demand quicker and more innovative and efficient solutions. Animal scientists around the globe currently face many challenging issues: from ensuring food security to prevent excess of nutrient intake by humans, from animal welfare to working with genetic-engineered animals, from carbon footprint to water footprint, and from improved animal nutrition to altering the rumen microbiome. Many of these issues are most likely to continue (or to exacerbate further) in the coming years, but animal scientists have many options to surmount the obstacles posed to the livestock industry through tools that are presently available. The frequency, interval, and intensity of livestock impacts, however, differ across regions, production systems, and among livestock species. These differences are such that the generalization of these issues is impossible and dangerous. For instance, when we discuss domesticated ruminant nutrition in the human food context, we look for the most efficient ruminant feeds that complement, rather than compete with, grains grown for direct human nutrition. Greater scrutiny and standardization are needed when developing and validating methodologies to assess short- and long-term impacts of livestock production. Failure in correctly quantifying these impacts may lead to disregard and disbelief by the livestock industry, increased public confusion, and the development of illusionary solutions that may amplify the impacts, thereby invalidating its original intent.
Keywords: challenges; issues; livestock; ruminant; production